Multiobjectective environmental departure procedure optimization - McEnteggart, Quintain; Whidborne, James F. (AIAA, 2018)
To achieve a sustainable future for air transport, the International Civil Aviation Organization has proposed goals for reductions in community noise impact, local air quality, and climate-impacting emissions. The paper focuses on the contribution aircraft operations make to those goals. It describes a multiobjective optimization methodology intended to support the planning of environmentally efficient departure procedures. The methodology treats the problem as a multiobjective optimal control problem that is solved through the application of a direct method of trajectory optimization and a multiobjective version of the differential evolution algorithm. The method generates Pareto fronts between several competing objectives, allowing the decision maker to make informed decisions about potential tradeoffs between different environmental goals. The methodology is demonstrated through its application to a real-world many-objective procedure optimization study. The method supports in-depth analysis of the problem not achievable through existing methods and is used to identify a solution set that offers improvements in all environmental objectives relative to the existing procedure design.